DESCENDING MOTION OF PARTICLES AND ITS EFFECT ON OZONE HOLE - IWASAKA, Yasunobu; KONDOH, Kouji; KAWAHIRA, Kohji (National Institute of Polar Research, 1989)
P(論文) The descending motion of the aerosol layer was observed by a lidar at Syowa Station. The particle size would be about a few micrometers or larger, if the descending motion was due to a gravitational sedimentation (Y. IWASAKA : Tellus, 38B, 364,1986). As shown in Fig. 1,the condition of super-saturation was not always satisfied for pure water vapor or nitric acid vapor even in mid-winter if the density profiles in mid-latitudes are assumed. Therefore the particle which settles to the region of P<P_D, where P and P_D are partial pressure of water vapor (or nitric acid vapor) and saturation pressure of them, respectively, evaporates the gases condensed in the particles. IWASAKA and KONDOH (Geophys. Res. Lett., 18,87,1987) showed that ozone depletion rate was largest near 15km and the second peak was near 10km and lower. The heights of these [figure] active ozone-loss regions do not correspond to the region where particle production rate is large. The height of the ozone-loss region is lower than that of active particle formation area. The descending motion of particles to the region where evaporation rate is high seems to occur the formation of Cl_2 and ClOH. departmental bulletin paper